2016
DOI: 10.1039/c6cc01250g
|View full text |Cite
|
Sign up to set email alerts
|

One-step electrochemical synthesis of nitrogen and sulfur co-doped, high-quality graphene oxide

Abstract: High-quality graphene oxide (GO) with high crystallinity and electrical conductivity as well as in situ doped with nitrogen and sulfur is obtained via the electrochemical exfoliation of graphite. Furthermore, iron incorporated GO sheets show promising catalytic activity and stable methanol tolerance durability when used as electrocatalysts for the oxygen reduction reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 29 publications
(32 reference statements)
2
50
0
Order By: Relevance
“…It has been shown that nearly pristine graphene with a C/O of 25.3 and mobility of 405 cm 2 ·V −1 s −1 could be synthesized within seconds by EC exfoliation of graphite foil 28 . Inspired by these successes, researchers also tried to synthesize GO by EC oxidation of various graphitic materials such as pencile core 29 , graphite rode 30 and graphite flakes 31 , 32 . Unfortunately, the accompanied water/solvent electrolysis process aggravates the expansion and delamination of graphitic materials, which lead to ineffective current supply or broken circuit before the desired EC oxidation process can be achieved 27 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that nearly pristine graphene with a C/O of 25.3 and mobility of 405 cm 2 ·V −1 s −1 could be synthesized within seconds by EC exfoliation of graphite foil 28 . Inspired by these successes, researchers also tried to synthesize GO by EC oxidation of various graphitic materials such as pencile core 29 , graphite rode 30 and graphite flakes 31 , 32 . Unfortunately, the accompanied water/solvent electrolysis process aggravates the expansion and delamination of graphitic materials, which lead to ineffective current supply or broken circuit before the desired EC oxidation process can be achieved 27 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…A reduced graphene with a very high C/O ratio (25.3) and high electron mobility has been synthesized within seconds by electrochemical exfoliation of graphite foil [23]. Analogously, GO has been produced by electrochemical oxidation of several graphitic materials in a variety of geometries such as pencil cores and graphite powders, foils, rods, or plates [24][25][26][27]. The reported approaches have emerged as promising and versatile alternatives to the chemical methods.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the presence of electronic conductivity of films in a dry atmosphere can be a qualitative criterion for a small degree of functionalization of FLGS surface. However, in our case, the oxygen content in FLGS is sufficiently high and electronic conductivity should be explained by the fact that functional groups are mainly concentrated at the edges of graphene planes, and basal planes themselves do not undergo significant changes compared to the original graphite [20].…”
Section: Resultsmentioning
confidence: 57%
“…Data obtained for the edge of the film formed by c-FLGS is presented in Figure 2 [18,19] suggests that oxygen-containing functional groups on the surface of FLGS are represented by epoxy (286.7 eV), hydroxy (285.3 eV), and carboxyl (288.7 eV) groups ( Table 1). The deconvolution of the S2p peak (Figures 3(c) and 3(f)) reveals the presence of C-SO 3 group at 169.6 eV for both samples and C-SO 2 at 168.4 eV for c-FLGS [20]. Figure 4 shows current-time curves of FLGS films, obtained by plasma-assisted electrochemical exfoliation of graphite using cathodic (curve 1) and anodic plasma (curve 2).…”
Section: Resultsmentioning
confidence: 99%